TianGong database—an open-source, ILCD entry-level life cycle unit process database of china - Ming Xu; Weiqiang Chen; Yutao Wang; Lei Shi; Zhi Cao; Huimin Chang; Chang Chen; Xiangbin Ding; Jianwei Du; Huabo Duan; Kai Fang; Cuiyang Feng; et al. (Journal of Industrial Ecology, 2026)

Fine-scale mangrove species monitoring and ecological threshold assessment for coastal management in Quanzhou Bay, China - Siming Chen; Fei Chen; Longhui Niu; Zhong Deng; Kebin Wu; Wenbin Li (Environmental Monitoring and Assessment, 2026)

Cross-media transfer footprint control for sustainable environment management – a perspective from wastewater treatment - Yujun Huang; Yipeng Wu; Xipeng Yu; Miao Li; Kebin He; Shuming Liu (Water Research, 2026)

Polysaccharide gel beads co-loaded with yeast and insecticide for sustainable and targeted control of subterranean pests via attract-and-kill strategy - Chenglong Cui; Zhimin Wang; Ertao Li; Wenjie Shangguan; Xiaohu Wu; Jiao Yin; Kebin Li (Chemical Engineering Journal, 2025)

Strategic approach to reduce environmental damage by CO2 and air pollution based on Energy-Material-Emission Nexus: Insights from Beijing - Daiwei Ouyang; Qingru Wu; Shuxiao Wang; Kaiyun Liu; Shengyue Li; Yao Li; Xinyun Chen; Kun Wang; Wenhao Wu; Zhaoxin Dong; Yueqi Jiang; Yanning Zhang; et al. (Resources, Conservation and Recycling, 2025)

Synergistic reduction of air pollutants and carbon dioxide emissions in Shanxi Province, China from 2013 to 2020 - LiLing Wu; Shida Sun; Gaige Zhang; Zimu Jia; Yuyun Liu; Chenxi Xu; Mengjie Guo; Luyao Zhang; Cilan Cai; Runcao Zhang; Jialin Zheng; Wenjie He; et al. (Science of The Total Environment, 2024)

Upcycling of polyethylene/polypropylene mixtures promoted by well-controlled multiblock olefin copolymers - Yuze Kang; Hanlin Wang; Fanmao Meng; Shangtao Chen; Bin Du; Zihao Jiang; Jiajia Wu; Kebin Zhang; Huan Gao; Li Pan; Yuesheng Li (Chemical Engineering Journal, 2024)

Mid-infrared superconducting nanowire single photon detector enhanced by overcoupled metasurfaces - Yue Dai; Fengjie Zhu; Kebin Fan; Qi Chen; Labao Zhang; Fei Zhou; Yue Fei; Hang Yuan; Hongkai Shi; Hao Wang; Xiaoqing Jia; Qingyuan Zhao; et al. (Science Bulletin, 2024)

A Review on Brown Carbon Aerosol in China: From Molecular Composition to Climate Impact - Xubing Cao; Jiumeng Liu; Yuliang Wu; Yuan Cheng; Mei Zheng; Kebin He (Current Pollution Reports, 2024)

Changes in Mental Health and EEG Biomarkers of Undergraduates Under Different Patterns of Mindfulness - Miaoling Luo; Quan Gan; Ziyang Huang; Yunxiong Jiang; Kebin Li; Minxiang Wu; Dongxiao Yang; Heng Shao; Yanmei Chen; Yu Fu; Zhuangfei Chen (Brain Topography, 2024)
The effects of short-term mindfulness are associated with the different patterns (autonomic, audio guided, or experienced and certified mindfulness instructor guided mindfulness). However, robust evidence for reported the impacts of different patterns of mindfulness on mental health and EEG biomarkers of undergraduates is currently lacking. Therefore, we aimed to test the hypotheses that mindfulness training for undergraduates would improve mental health, and increase alpha power over frontal region and theta power over midline region at the single electrode level. We also describe the distinction among frequency bands patterns in different sites of frontal and midline regions. 70 participants were enrolled and assigned to either 5-day mindfulness or a waiting list group. Subjective questionnaires measured mental health and other psychological indicators, and brain activity was recorded during various EEG tasks before and after the intervention. The 5-day mindfulness training improved trait mindfulness, especially observing (p = 0.001, d = 0.96) and nonreactivity (p = 0.03, d = 0.56), sleep quality (p = 0.001, d = 0.91), and social support (p = 0.001, d = 0.95) while not in affect. Meanwhile, the expected increase in the alpha power of frontal sites (p < 0.017, d > 0.84) at the single electrode level was confirmed by the current data rather than the theta. Interestingly, the alteration of low-beta power over the single electrode of the midline (p < 0.05, d > 0.71) was difference between groups. Short-term mindfulness improves practitioners’ mental health, and the potentially electrophysiological biomarkers of mindfulness on neuron oscillations were alpha activity over frontal sites and low-beta activity over midline sites.

Analysis of Influence of Baicalin Joint Resveratrol Retention Enema on the TNF-α, SIgA, IL-2, IFN-γ of Rats with Respiratory Syncytial Virus Infection - Kebin Cheng; Zhenghua Wu; Beilan Gao; Jinfu Xu (Cell Biochemistry and Biophysics, 2014)